STUDI PENGEMBANGAN PROTOTYPE KNOWLEDGE MANAGEMENT SYSTEM PADA BIMBINGAN KONSELING TINGKAT SMP DI SALATIGA - Friscilia, Michelle; Beng, Jap Tji; Tiatri, Sri (Jurnal Ilmu Komputer dan Sistem Informasi, 2013)
In schools’ context, one of many concerns of teachers is the changes of students’ behavior. To support quality education, the role of teachers, especially the counseling teachers is needed. Therefore, to give a good performance, education must be supported with good knowledge management. This study aimed to develop and test a prototype knowledge management system to help counseling teachers. The most important theory used is knowledge management system and technology acceptance models. Interviews with three teachers were used as the information basis for development of a prototype that included a course categories, repository and discussion features. Then the prototype was showed to the 18 guidance and counseling teachers, who were covered two third of guidance and counseling teachers in Salatiga. The results obtained in this study are: (a) Prototype of knowledge management system can help guidance and counseling teachers in overcoming problems at school or work, (b) teacher of guidance and counseling had received well the existence of this prototypes, and (c) the variables of perceived ease of use and perceived usefulness have significant influence on behavioral intention to use the prototype of knowledge management system. The guidance and counseling teachers were eager to use the prototype of knowledge management system. Key words Knowledge management system, guru bimbingan konseling, actor network theory, prototype, technology acceptance model